The magic of thinking big : the true secret of success-how to earn more, lead fearlessly and live a happier life - Schwartz, David (London : Vermilion, 2016)
First published in 1959, David J. Schwartz's classic teachings are as powerful today as they were then. Practical, empowering and hugely engaging, this book not only inspires, it gives you the tools to change your life for the better - starting from now. His step-by-step approach shows you how to: defeat disbelief and the negative power it creates; make your mind produce positive thoughts; plan a concrete success-building programme; do more and do it better by turning on your creative power; and capitalise on the power of now! Revised for today's reader, it offers a go-to guide to a better life - starting with the way you think.
Keywords: Success; Self-confidence.; Level of aspiration